Aspectos fisiológicos e fitoquímicos de Bauhinia forficata Link e Plantago major L. - Clemente Filha, Ana Cardoso (1996)
Bauhinia forficata Link and Píantago major L. are species utilized as medicinals owing to their antidiabetical and antiinflamatorical, respectively. This work had as purpose to characterize active substances in terms of the plant age and photoperiod as well as the study of the germination of these species. Leaf extracts of mature and young plants of B.forficata were subjected to fractioning by several sorts of chromatography techniques. Annd alkaloids and tannins were not detected at all. The flavonoids identified were Kaempferol-3-0-(gly-rham-xyl) and kaempferol-3-0 (gly- rham). Qualitatively, differences were not observed in the flavonoidic profiles of young annd mature plants. To Plantago major, analysis for flavonoids and mucilages in plant ssubmitted to photoperiodical regimes of 8 h, 16h and natural (12 h) was performed. No differences were observed in the flavonoidic profile of the three photoperiodic treatments. The isolated flavonoids were luteolin glycosides based on glucose and glucuronic acid. There were different in the mucilage content in the three photoperiods, being that of 16 h showed the gratest mucilage content annd the natural photoperiod the smallest. The mucilage of Píantago is made up of arabinose, galactose and glucuronic acid. Concerning germinnation the effects of light, temperature and different concentrations of GAs were analysed. The seeds of Bauhinia are indifferent to light, showed highest germination percentage at 20 and 30/20° C and did not respond to the application of GA3. The Plantago seeds showed positive photoblastism and best germination rate at 30-20° C, no germination at 20 °C.